Pengaruh Konsumsi Telur Ayam Rebus dan Madu Pada Remaja Puteri dengan Anemia Defisiensi Zat Besi - Sartika, Tri (REAL in Nursing Journal, 2024)
Background: Anemia is a condition in which the number of red blood cells or the concentration of hemoglobin in them is lower than normal. Anemia in teenagers is still very high at over 20%. In detail, anemia in children aged 5 to 14 years is 26.8%, aged 15 to 24 years is 32%, meaning that 3 out of 10 people experience anemia. The impact of anemia if it occurs in adolescent girls and women of childbearing age is decreased body endurance, decreased fitness and agility of thinking, as well as decreased learning achievement and work productivity/performance. This research aims to find out the effect of consuming boiled chicken eggs and honey on adolescent girls with iron deficiency anemia. Methods:The research design used wa a pre-experimental design with the form of a one group pretest-posttest design at Sriwijaya Junior High School, Palembang, South Sumatra, The number of samples in the research was 13 respondents. The instrument used was an observation sheet, a tool for measuring Hb levels using an Hb Meter (Easytouch GCHb Model ET-321).  The researcher carried out bivariate analysis, namely using the paired T test. Results: The average Hb in the first measurement (pretest) was 11.46 gr/dL, with a standard deviation of 0.32 gr/dL. In the second measurement (posttest), an average Hb level was found to be 11.73 gr/dL, with a standard deviation of 0.31 gr/dL. It can be seen that the mean difference between the first and second measurements is 0.26, with a standard deviation of 0.34. Conclusion: The statistical test results obtained a value of 0.014, so it can be concluded that there was a significant difference between the HB levels of the first and second measurements at Sriwijaya Junior High School, Palembang, South Sumatra.Pengaruh Konsumsi Telur Ayam Rebus dan Madu Pada Remaja Puteri dengan Anemia Defisiensi Zat Besi